(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the usability of the gel for use in gloves for better handling with adhesive tapes. To this end, an exploratory-descriptive study with a qualitative approach was carried out, carried out at the Hospital School, with nursing assistants who received gel for carrying out their work activities in procedures involving the use of gloves and tape. In view of the analysis, it was possible to reflect that the difficulties experienced during the use of gloves in procedures that contain the use of adhesive tape became evident as thematic categories; breaking the gloves and wasting material; difficulties and impairment of care related to the gloves-adhesive association; the benefits of the gel during assistance actions. Given the above, it was possible to conclude that the use of gel as a technology to prevent adhesion between the gloves and the adhesive tape due to the glue is positive and has usability that tends to favor the assistance not only of nursing professionals, but of the various professionals of health.